Applications of Waqf-featured Fund In The Malaysian Islamic Fund Management Industry: A Comparative Study - Muhammad Taqi'uddin Mohd Hamzah; Syahnaz Sulaiman; Muhammad Iqmal Hisham Kamaruddin; Aznan Hasan (Universiti Sultan Azlan Shah (USAS), 2024)
Indexed by Scopus/MyCite